The Quality of Educational Services from Viewpoints' Of Dentistry Students of Gorgan In 2021 - Alireza Heidari; Zahra Khatirnamani; Mehdi Abbasabadi; Narges Rafiei; Marzieh Ahmadi; Hadiseh Saravani (Mashhad University of Medical Sciences, 2023)
Background: The notion of educational service quality is multifaceted and arises from the perceived variance between students' expectations from the educational system and the services they actually receive. The progression of universities has shifted from a quantitative phase to a qualitative one, and as such, it has become necessary to assess the quality of university services. This research was conducted to evaluate the educational service quality at Gorgan Dental School.Materials and Methods: A cross-sectional descriptive study was conducted in 2021, among dental students attending Gorgan Dental School, Golestan University of Medical Sciences. Data were collected using the SERVQUAL model questionnaire, which was devised considering the five domains of service quality. Descriptive statistics and inferential statistics were used in SPSS 23 to analyze the data.Results:  A total of 103 students, with an average age of 23. 09±3. 31 years, participated in this study. Most of the students were female (59%) and the rest were male (44%). The average overall score of expected service quality was 4.52±0.49 and the overall average score of perceived service quality was 3.09±0.71. The overall average gap in service quality was -1.44±0.79. The greatest gap was noticed in the responsiveness domain (-1.58±1.05) and the least gap was found in the tangible domain (-23.1±0.92).Conclusion: There was a gap in all aspects of the quality of educational services and related terms, which shows that the expectations of students have not been completely met. In order to resolve this gap, meticulous planning and effective management of educational services should be enacted.